2019
DOI: 10.1371/journal.pone.0211094
|View full text |Cite
|
Sign up to set email alerts
|

The use of initial dosing of gentamicin in the management of pyelonephritis/urosepsis: A retrospective study

Abstract: ObjectiveThe primary objective was to determine if initial empirical intravenous dosing of gentamicin improved patient's outcomes in pyelonephritis/urosepsis compared with alternative IV antibiotic management.DesignRetrospective cross-sectional descriptive study.SettingPublic TertiaryTeaching Hospital serving adults in an urban centre.ParticipantsAll adult patient records with a recorded diagnosis of any of pyelonephritis/urosepsis, urinary tract infection, UTI, complicated urinary tract infection, bacteriuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
2
0
3
Order By: Relevance
“…30 In another study, empirical intravenous ( IV) antibiotic treatment prescribed for 152 patients with severe UTI showed that the overall duration of IV antibiotic treatment was significantly shorter for patients administered gentamicin empirically as initial treatment compared with patients who were not administered gentamicin at all. 31 Hence, we agree with this study and recommend the use of gentamycin as an empirical therapy for a short time, which is also in accordance with the study of Ekmen et al, who concluded that "gentamicin does not affect the hearing test when it is used in the short-term (5-7 days)". 32 The fluctuation among different centers confirms the requirement for local resistance prevalence data to be made available to professionals treating UTIs, particularly where empirical treatment is being utilized for urinary infections.…”
Section: Discussionsupporting
confidence: 91%
“…30 In another study, empirical intravenous ( IV) antibiotic treatment prescribed for 152 patients with severe UTI showed that the overall duration of IV antibiotic treatment was significantly shorter for patients administered gentamicin empirically as initial treatment compared with patients who were not administered gentamicin at all. 31 Hence, we agree with this study and recommend the use of gentamycin as an empirical therapy for a short time, which is also in accordance with the study of Ekmen et al, who concluded that "gentamicin does not affect the hearing test when it is used in the short-term (5-7 days)". 32 The fluctuation among different centers confirms the requirement for local resistance prevalence data to be made available to professionals treating UTIs, particularly where empirical treatment is being utilized for urinary infections.…”
Section: Discussionsupporting
confidence: 91%
“…25 Penggunaan antibiotik profilaksis selain karbapenem memiliki kecenderungan urosepsis lebih tinggi (31,6% vs. 9,5%, p = 0,057). 26 Menurut Ryan, James et al 27 , bahwa penggunaan co-amoxiclav (52%), memiliki pola resistensi tertinggi dibanding antibiotik yang lain, karena tingginya penggunaan, antibiotik dengan angka resistensi yang tinggi memiliki potensi menjadi urosepsis dengan multi-drug resistant (MDR), sehingga perlu dihindari. 14 Bakteri gram negatif merupakan penyebab terbanyak urosepsis, terutama Escherichia coli dan Klebsiella pneumoniae.…”
Section: Pembahasan Penggunaan Antibiotikunclassified
“…Studi lain mengatakan bahwa penggunaan kombinasi dengan gentamisin (4 -6 mg/kg dosis tunggal IV) tidak memberikan hasil yang signifikan dalam terhadap lama rawatan (median = 5 hari) 27 . Hal ini tidak menghasilkan kesimpulan yang sama dengan penelitian dasar pada negara yang sama, yang menyebutkan penggunaan 54% strain E. coli pada urine, sensitif terhadap penggunaan gentamisin.…”
Section: Pembahasan Penggunaan Antibiotikunclassified
See 1 more Smart Citation
“…The use of gentamicin, in parenteral administration, has shown significant better infection outcomes involving some gram-negative bacteria such as Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , and was also efficient against some other strains such as Neisseria [ 5 , 6 , 7 ]. Gentamicin also proved to be efficient in bacterial septicemia, meningitis, peritonitis, endocarditis, pneumonia, urinary tract infections, or odontogenic infections [ 8 ].…”
Section: Introductionmentioning
confidence: 99%